Impact of 10-valent pneumococcal conjugate vaccine on pneumococcal meningitis in children up to two years of age in Brazil - Indianara Maria Grando; Camile de Moraes; Brendan Flannery; Walter Massa Ramalho; Marco Aurélio P. Horta; Diana Lucia Moura Pinho; Gilmara Lima Nascimento (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The objective of this study was to analyze the impact of vaccination against Streptococcus pneumoniae on the morbidity and mortality from pneumococcal meningitis in children ≤ 2 years in Brazil, from 2007 to 2012. This is a descriptive study and ecological analysis using data from the Information System on Notifiable Diseases. Pre-vaccination (2007-2009) and post-vaccination (2011-2012) periods were defined to compare incidence rates and mortality. A total of 1,311 cases and 430 deaths were reported during the study period. Incidence decreased from 3.70/100,000 in 2007 to 1.84/100,000 in 2012, and mortality decreased from 1.30/100,000 to 0.40/100,000, or 50% and 69% respectively, with the greatest impact in the 6-11 month age group. This decrease in Pneumococcal meningitis morbidity and mortality rates two years after introduction of the 10-valent pneumococcal conjugate vaccine suggests its effectiveness.